Microdon dentigiganteum sp. nov. and other Microdontinae species (Diptera: Syrphidae) from Northeast China - Tian, Jing; Huo, Ke-Ke; Zhang, Chun-Tian; Ren, Bing-Zhong (Zootaxa, 2019)
Hoverflies (Diptera: Syrphidae) of the subfamily Microdontinae were surveyed in Northeast China. A total of six species were identified, including one new to science, Microdon dentigiganteum sp. nov. from Liaoning. This new species has a pair of very large-size posterior calcars on the scutellum and very wide flat tarsi. New records of Metadon spuribifasciatus (Huo, Ren et Zheng, 2007), Microdon analis (Macquart, 1842) and Microdon auricomus Coquillett, 1898 from Jilin province, and Microdon ignotus Violovitsh, 1976 and Microdon oitanus Shiraki, 1930 from Liaoning province are provided. A key to the six studied species and diagnostic figures are presented.